P106 Sputum Induction Reduces The Need For Bronchoscopy In School-aged Children With Cystic Fibrosis. (10th November 2014) - Collins, N; Robson, K; Nagakumar, P; Saglani, S; Voase, NWG; Davies, JC
Abstract : Background: Early detection of organisms such as Pseudomonas aeruginosa in CF is essential for successful eradication but is difficult in children, relying largely on non-invasive methods such as cough swabs (C/S) with sub-optimal sensitivity and specificity. Bronchoalvelolar lavage (BAL) remains the gold standard but disadvantages are its invasive nature, high cost and inability to be performed frequently. Sputum induction (SI) has previously been reported as a useful and safe technique in young children with CF, but it is not yet widely used. Hypothesis As part of a quality improvement initiative, we hypothesised that SI would reduce the need for BAL in school-aged CF children with deteriorating lung function and no significant bacterial growth on CS. Methods: After CS and bronchodilator, 7% hypertonic saline was nebulised via an ultrasonic Ultraneb (DeVilbiss Healthcare) for 15 min. Spirometry was performed pre, post and at 5 min intervals throughout. Sputum was collected at 5 min intervals, and at the end of the procedure physiotherapy was performed to collect more sputum. If a child was unable to expectorate then a CS or oropharyngeal (OP) suction was performed. Results: 39 children (41% male), median age 11 years (range 5–16 years), median FEV1 85% (range 39–112%) performed SI from June 2102 to July 2014. Significant bronchoconstriction occurred in 11%. 2 adverse events occurred (vomiting and dizziness). The procedure took a mean of 90 min including equipment set up and cleaning. 34/39 (87%) expectorated a sputum sample of which 15 (38.5%) had a positive bacterial culture; only 3 of these patients (20%) grew the same organism on the preceding CS. Five patients avoided planned BAL due to a positive SI result and 2 avoided an admission for intravenous antibiotics. Conclusion: SI is well tolerated in the majority of school-aged children with CF. It has a higher rate of positive bacterial culture than same-day CS and, in this cohort, avoided the need for bronchoscopy in a significant proportion. It is a time-consuming procedure, but based on these data, we consider that establishing SI as a clinical procedure will be a priority for our service.